Clinical severity grading of NF2-related schwannomatosis - Anna C. Lawson McLean; Denise Löschner; Said Farschtschi; Nora F. Dengler; Steffen K. Rosahl (Orphanet Journal of Rare Diseases)
Abstract Background NF2-related schwannomatosis (NF2) is associated with various tumors of the central and peripheral nervous system. There is a wide range of disabilities these patients may suffer from and there is no validated clinical classification for disease severity. We propose a clinical classification consisting of three severity grades to assist in patient management. Methods Patient records from 168 patients were screened for most common diagnoses with severe impact on everyday tasks, social interactions and life expectancy. Eight main categories were identified. One point was assigned to each category. Three severity grades were differentiated as follows: grade 1 (mild NF2): 0 points; grade 2 (moderate NF2): < 3 points; grade 3 (severe NF2): ≥ 3 points. This grading system was then evaluated with respect to inter-rater reliability and clinical significance. Results The patients were grouped according to our new clinical grading system into grade 1 in 48% (n = 80), grade 2 in 43% (n = 72), and grade 3 in 10% of patients (n = 16). There was substantial inter-rater reliability between 3 raters with different levels of clinical experience (Fleiss’ kappa = 0.62). The severity grades correlated significantly with hospitalization, number of operations and dependency on implants (such as cochlear implant, auditory brain-stem implants or ventriculoperitoneal shunts). Conclusions Clinical disease severity of NF2 patients is reflected in a simplified and rater-independent score with three grades. The score facilitates communication for medical personnel of varying experience and backgrounds, and adds a clinical tool to decision-making and research.